PERANCANGAN UI/ UX MENGGUNAKAN METODE DESIGN THINKING BERBASIS APLIKASI PENJUALAN PADA USAHA BAKSO BAROKAH - Lestari, Novika Widya; Krisna, Dany Yudha (JUTECH : Journal Education and Technology, 2024)
The development of digital technology has had a major impact on various business sectors, including small culinary businesses such as Bakso Barokah located at Simpang Empat Merbau. In order to remain competitive, this business needs to follow digital developments by implementing a UI/UX-based sales application that aims to improve operational efficiency while providing a better customer experience. This study focuses on application development using the Design Thinking method approach, which consists of five main stages: Empathize, Define, Ideate, Prototype, and Test. Through this approach, surveys and data collection were conducted through online questionnaires, as well as the creation of empathy maps, user personas, and user flows. The results of this application design succeeded in creating a system that simplifies the ordering process, stock management, and improves interaction with customers. Prototype testing using the System Usability Scale (SUS) method produced an average score of 86, indicating that this application was well received and quite easy to use by its users. This study provides a solution for Bakso Barokah in overcoming operational challenges while improving customer service with a more modern and efficient approach. For future development, it is recommended that this application be more responsive and equipped with customer loyalty features to increase user retention.